2006
DOI: 10.1590/s1677-04202006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of water soluble carbohydrates in vegetative tissues of Lolium multiflorum Lam. ssp. italicum cv. Lema

Abstract: In temperate grasses, fructans are the major storage polysaccharides, being accumulated mainly in mature leaf sheaths, and also in the roots. The partitioning of carbohydrates within different organs regulates plant growth and development. The aim of the present work was to analyze the partitioning of water soluble carbohydrates in five different parts (elongating leaf blades, expanded leaf blades, upper and lower segments of the stubble, and roots) of plants of L. multiflorum cv. Lema, in order to contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Donaghy and Fulkerson (1998), however, reported greater WSC concentration at a higher stubble height (5.0 cm) compared to a lower stubble height (2.0 cm). Also, contrary to our results, Sandrin et al (2006) found no difference in the WSC concentration in the upper and lower stubble of annual ryegrass. Stubble WSC content, which is a better indicator of forage crop regrowth potential than concentration (Donaghy & Fulkerson, 1998), was greater for Maximus than for Marshall, and this can be explained by both the greater WSC concentration and stubble weight of Maximus than Marshall.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Donaghy and Fulkerson (1998), however, reported greater WSC concentration at a higher stubble height (5.0 cm) compared to a lower stubble height (2.0 cm). Also, contrary to our results, Sandrin et al (2006) found no difference in the WSC concentration in the upper and lower stubble of annual ryegrass. Stubble WSC content, which is a better indicator of forage crop regrowth potential than concentration (Donaghy & Fulkerson, 1998), was greater for Maximus than for Marshall, and this can be explained by both the greater WSC concentration and stubble weight of Maximus than Marshall.…”
Section: Discussioncontrasting
confidence: 99%
“…Water‐soluble carbohydrates are a major contributor to the regulation of growth and development in temperate grasses, and compared to other plant parts, the stubble of these grasses is known to contain the greatest concentration of WSC (Sandrin, Domingos, & Figueiredo‐Ribeiro, ). The magnitude of reduction in reserve levels of WSC varies with the frequency and severity to which plants are defoliated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the 160-ppb ozone experiment suggest that other enzymatic antioxidant such as catalase (not measured in the present work) was active and could have contributed to decreasing H 2 O 2 levels (Corpas et al 1999). The role played by APX as an important antioxidant in Italian ryegrass could be corroborated by the lower H 2 O 2 levels in the leaf blades, where such enzyme is prevalent, in opposition to the fructan which is accumulated mostly in the leaf sheaths (Sandrin et al 2006).…”
Section: Discussionmentioning
confidence: 96%